Learning Management of The Qur’an Memorization Using Classical Method of Scrutinized Reading in Yayasan Hidayatul Mustafid Batam - Imam Mutowali (Nalar Global Foundation, 2020)
The method of memorizing Qoran is developing rapidly in Indonesia. However, many of them were not managed well. Weaknesses in the management affected the results of achievement in terms of quality and quantity of memorization and recitation. This descriptive qualitative research aimed to find out and analyze the management of Qoran memorization learning by applying Classical method: reciting and listening at Hidayatul Mustafid Foundation in Batam and the factors that influence the success of that management. The data collection techniques included observation, interview, documentation, and triangulation. Furthermore, the collected data were analyzed by using data reduction, data display, and conclusion drawing/verification. Based on the results, it was concluded that the management of Qoran memorization learning by using classical method: reciting and listening was carried out according to the standard of good management. Planning that referred to the curriculum, operational guidelines, and technical coordinator guidelines took place before the learning process. In addition, organizing was carried out by prescribing jobs and duties of all personnel and classifying learning into two phases. Furthermore, controling was carried out by observing the implementation of learning, teachers-students interaction, and the achievement of teaching objectives through supervision (directly) and reports in meetings (indirectly). Students’ memorization was controlled through muraja'ah (reviewing). Evaluation was carried out in the forms of teacher’s’ daily evaluation, chapter memorization increase evaluation, and examination by the head of the institution.